Does insomnia worsen cardiometabolic health? - Gewei Zhu; Kirstie Anderson (Advances in Clinical Neuroscience & Rehabilitation, 2019)
Insomnia is thought to affect 5-10% of the general population and is associated with daytime impairment and distress. Insomniacs were found to have a higher risk of poor cardiometabolic health. However, this association is only significant if they have both insomnia and objective short sleep duration.